2007
DOI: 10.1007/s00428-007-0406-7
|View full text |Cite
|
Sign up to set email alerts
|

Claudin expression in pancreatic endocrine tumors as compared with ductal adenocarcinomas

Abstract: Altered expression of recently described claudins (CLDNs) as members of tight junction (TJ) transmembrane proteins was noted in several malignancies. We aimed to analyze protein and messenger RNA (mRNA) expressions of different CLDNs in human pancreatic endocrine tumors (PET) and ductal adenocarcinomas. A total of 45 formalin-fixed, paraffin-embedded samples were studied. Immunohistochemistry and real-time reverse transcriptase polymerase chain reaction analysis were carried out for quantification of CLDN 1, -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 42 publications
2
46
0
Order By: Relevance
“…Claudin expression alterations in primary cancers are much better characterized, including those of the breast (Kominsky et al 2003;Tokes et al 2005), colon (de Oliveira et al 2005;Dhawan et al 2005), prostate (Long et al 2001), and pancreas (Nichols et al 2004;Borka et al 2007). Our group has also previously defined tight junctional protein changes in primary and metastatic cancers of the liver.…”
mentioning
confidence: 99%
“…Claudin expression alterations in primary cancers are much better characterized, including those of the breast (Kominsky et al 2003;Tokes et al 2005), colon (de Oliveira et al 2005;Dhawan et al 2005), prostate (Long et al 2001), and pancreas (Nichols et al 2004;Borka et al 2007). Our group has also previously defined tight junctional protein changes in primary and metastatic cancers of the liver.…”
mentioning
confidence: 99%
“…These discrepant results may be due to the difference between number and characteristics of the cases of the studies. Borka et al (2007) showed expression of Claudin 1, 4 and 7 in pancreatic adenocarcinoma (Borka et al, 2007). Tsukahara et al (2005) investigated the expression of claudin-4 in human pancreas, pancreatic ductal adenocarcinomas, and intraductal papillarymucinous tumors of the pancreas (IPMT), and compared with that of claudin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin-3 and -4 are expressed in many normal organs and are overexpressed in several carcinomas, including colorectal, breast, ovary, prostate and pancreatic carcinomas (4)(5)(6)(7)9), and these proteins are receptors for cytotoxic Clostridium perfringens enterotoxin (CPE) (23,24). CPE is known to injure intestinal epithelial cells expressing claudin-3 and/or -4 by increasing membrane permeability, leading to loss of osmotic equilibrium and subsequent cytolysis and cell death (25).…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity was evaluated as described previously (7,10,13). Ten randomly selected fields in each tissue slide were analyzed using high-power field (x400) with 100 cells counted per field.…”
Section: Evaluation Of Immunoreactivity and In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation